RITUAL WUDHU : UPAYA MENJAGA KESEHATAN TUBUH DENGAN PERAWATAN SPIRITUAL - Heru Syahputra (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
The religious concern for health problems is amazing. That is partly because various human activities in worship are inseparable from the element of health. How do Islamic teachings see this? Islam considers health as one of the greatest favors of Allah SWT. In worship such as prayer, it is required in advance to take ablution. Ablution is not just cleaning zhahir limbs, it is also not just purifying the body regularly several times a day, but the mental and glory influence felt by a Muslim after ablution is deeper than what is expressed by words, especially if ablution it is done perfectly and thoroughly. Ablution has a big role in the life of a Muslim. Ablution makes a Muslim always aware, excited and shining.Keywords: Ablution; health; Islam.